The Role of Environmental Accounting in Preserving Cultural Heritage: A Case Study in Tenganan Pegringsingan Village, Bali, Indonesia - Komang Adi Kurniawan SAPUTRA; Nyoman Ari Surya DHARMAWAN (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study explores the role of environmental accounting in preserving cultural heritage, focusing on Tenganan Pegringsingan Village, Bali, Indonesia. This village is known for its unique traditions and culture, which are threatened by modernization and the exploitation of natural resources. Environmental accounting, which integrates economic, social, and environmental aspects, is expected to make a significant contribution to resource management and local cultural preservation. The research method used is a qualitative approach with data collection through in-depth interviews, participant observation, and document analysis. The results of the study indicate that the application of environmental accounting not only increases public awareness of the importance of cultural preservation but also encourages active participation in sustainable natural resource management. In addition, environmental accounting plays a role in creating transparency and accountability in resource use, which in turn strengthens the cultural identity of the community. This study contributes to the understanding of how environmental accounting can be a strategic tool in efforts to preserve cultural heritage, as well as providing recommendations for policymakers to integrate environmental accounting practices in cultural and environmental management in tourist areas.